Synthesis and Reactions of 1,3,5-Tri- and 1,3,5,7-Tetracarbonyl Compounds - Langer, Peter (Synlett, 2021)
The reaction of 1,3-bis(silyloxy)-1,3-butadienes with functionalized and nonfunctionalized acid chlorides and bis(acid chlorides) gives rise to the formation of a great variety of 1,3,5-tri- and 1,3,5,7-tetracarbonyl compounds and cyclic products derived from them. Examples include functionalized and nonfunctionalized 3,5-dioxopentanoates, 3,5-dioxopimelates, 3-alkylidene-3H-isobenzofuran-1-ones, salicylates, 3(2H)furanones, and 3-oxo-4-sulfonylesters. Methylation and cyclopropanation reactions of 1,3,5-tri- and 1,3,5,7-tetracarbonyl compounds do not provide access to the expected permethylated and cyclopropanated polycarbonyl compounds. However, the latter could be prepared by stepwise protocols. The reaction of 1,3,5-tri- and 1,3,5,7-tetracarbonyl compounds with dinucleophiles resulted in cyclization reactions to give a variety of heterocyclic structures.1 Introduction2 Reactions of 1,3-Bis(silyloxy)-1,3-butadienes with Acid Chlorides3 Reactions of 1,3,5-Tri- and 1,3,5,7-Tetracarbonyl Compounds4 Conclusion
Keywords: carbonyl compounds; condensation reactions; cyclopropanes; heterocycles; silyl enol ethers